Informal Banking and Early International Entrepreneurs: The Case of the Chettiars - TAN, Jayarani (Institutional Knowledge at Singapore Management University, 2012)
As moneylenders during nineteenth century colonial period the Chettiars were functioned as informal bankers in Asia. They began as communal entrepreneurs in their clan but grew beyond their domestic borders. Despite their smallness and resources, they were able to internationalize. This paper reports a study into their internationalization examining the manner they were able to successfully venture abroad. We found that external factors like the British protectorate and internal factors like their unique socio-cultural institutions and norms and values served as enabling factors for their internationalization. These include a family culture of training the sons for the business, embracing business best practices, replicating domestic social structures overseas and the Chettiar community abroad. The social structures extended overseas provided the social support network for Chettiars leaving their homes and the overseas Chettiar community provided the networks for international expansion.